The Effectiveness of Using Cells at Work Anime Media on Students' Learning Outcomes in the Material of Cells in Blood Circulation and Immunity - Peniyanti Laila Alfina; Sauqina Sauqina; Maya Istyadji (Journal of Mathematics Science and Computer Education, 2024)
AbstractIndonesian society can easily access information and media through the internet. One of the animation video media easily accessible to all segments of Indonesian society is Japanese Animation, known as Anime. Anime has various interesting stories, one of which is Hataraku Saibou, which tells the activities of cells in the human body in the form of a narrative. This raises the question of whether anime with themes depicting the lives of working cell characters in the body can be used as a learning media for students to understand the explanation of cell activities in the body in a narrative form in the anime. Research has been conducted on the Hataraku Saibou Anime among the general public. It is said that this anime effectively increases public understanding of the human body system. However, there has been no study on the effectiveness of this anime when used in the learning process for students. Therefore, a study was conducted on Hataraku Saibou Anime, with the research objective of determining the effectiveness of the animation media of Hataraku Saibou anime. The research method used a Non-equivalent Control Group Design, an experimental class research with the treatment of watching Hataraku Saibou anime, and the control class with PowerPoint learning selected under certain conditions. Data was collected using pre-test and post-test question evaluation with validated RPP Instruments. The research results, analyzed by comparing the improvement of experimental and control class scores, were calculated using hypothesis testing with SPSS 21. It was found that using the t-test, the value obtained was 2.087 with a significance of 0.000. The critical value (t-crit) is 1.986. So it can be concluded that t-value is greater than t-crit (2.087 > 1.986). From this result, it can be concluded that the animation media of Hataraku Saibou anime is effective in the material of cells in the bloodstream and immune system.